Arthroscopic Bankart Repair and Open Bristow Procedure in the Treatment of Anterior Shoulder Instability With Osseous Glenoid Lesions in Collision Athletes. Issue 5 (28th May 2021) - Tasaki, Atsushi; Morita, Wataru; Nozaki, Taiki; Yonekura, Yuki; Saito, Masayoshi; Phillips, Barry B.; Kitamura, Nobuto
Background: Traumatic anterior shoulder instability in collision sports athletes often involves osseous glenoid lesions, which make surgical treatment challenging. High redislocation rates have been seen in collision sports athletes treated using arthroscopic Bankart repair. Purpose: To investigate the effectiveness of a combined arthroscopic Bankart repair and open Bristow procedure for the treatment of traumatic anterior shoulder instability in collision sports athletes, with a focus on osseous glenoid lesions. Study Design: Case series; Level of evidence, 4. Methods: We reviewed 149 shoulders in 141 competitive collision sports athletes (mean ± standard deviation age, 20.1 ± 4.1 years; 8 bilateral cases) who underwent a combined arthroscopic Bankart repair and open Bristow procedure with minimum 2 years of follow-up. Osseous Bankart lesions were arthroscopically reduced and fixed using a coracoid graft. Results: Clinical outcomes as indicated by mean Rowe score improved significantly from 50.0 preoperatively to 98.9 postoperatively ( P < .001) at a median follow-up of 3.4 years (range, 2.5-7 years). There were 2 recurrent dislocations (1.3%), both of which had nonunion of the transferred coracoid. Osseous Bankart lesions were observed in 85 shoulders, and osseous glenoid lesions ≥10% of the diameter of the nonoperative side were found in 58 shoulders, including 24 off-track cases. Clinical outcomes were not significantly different between patients with a glenoid defect ≥10% and <10%. Nonunion of the transferred coracoid was observed in 16 shoulders (10.7%), which had inferior Rowe scores; however, we could not define any risk factors for nonunion, including patient characteristics or bone morphology. Postoperative computed tomography performed in 29 patients >1 year after surgery showed successful repair of the osseous glenoid lesions, with a restored glenoid articular surface in all cases. Significant pre- to postoperative increases were seen in glenoid diameter (mean, 13.1% [95% CI, 9.9%-16.3%]; P < .001) and area (mean, 10.6% [95% CI, 8.5%-12.7%]; P < .001). Conclusion: A combined arthroscopic Bankart repair and open Bristow procedure improved bone morphology and was a reliable surgical method for treating collision sports athletes with traumatic anterior shoulder instability involving osseous glenoid lesions.